LOCAL TRADITIONS AND STRENGTHENING OF MULTICULTURAL VALUES IN DEVELOPING SOCIO-RELIGIOUS OF DELIMA SOCIETY - Emilia Susanti; Piki Setri Pernantah; Amirul Syafiq; Mehmed Ozay (Alfuad: Jurnal Sosial Keagamaan, 2022)
This research discusses local traditions that affect the solidarity and harmony of Delima communities, Tampan Subdistrict, Pekanbaru City. Delima society that is diverse both from ethnicity and religion is able to prioritize multicultural values through local traditions that are owned so as to develop socio-religious society. This research uses a qualitative research approach. The subject and location of this study is the community located in the Delima society of Pekanbaru. Informants in this study are determined according to qualitative research characteristics, namely by snowball sampling techniques. Data collection techniques are carried out by means of direct observation to the field, in-depth interviews, and documentation studies (literature). The results of this study explain several things, namely; 1) Forms of local traditions that developed in pomegranate communities, such as: Rewangan, Layatan and Gotong Royong; 2) Local traditions that promote multicultural values that can develop solidarity between different tribes and religions, unity and socio-religious people so that they can function in preventing social conflicts that occur between different tribes of religion.